Management of borderline ovarian tumors: A tertiary referral center experience in Egypt - Gaballa, Khaled; Abdelkhalek, Mohamed; Fathi, Adel; Refky, Basel; Belal, Khaled; elaraby, Moustafa; Zuhdy, Mohammad (Frontiers in Surgery, 2022)
Background: In this retrospective study we discuss our experience as a large tertiary referral center in Egypt in the management and follow up of borderline tumors Patients and methods: This is a retrospective cohort study where all patients who were diagnosed with a borderline ovarian tumor at the Oncology Center Mansoura University from November 2014 to June 2020 were included. Demographics, preoperative, operative, postoperative, pathologic, and oncologic follow-up data were retrieved from a prospectively maintained electronic database. The included patients were followed till April 2022. Results: We included 27 patients with borderline ovarian tumors. The mean age of the study patients was (47.67±16.39 years). The median CA 125 was 33 (6-304 U/ml). Frozen section examination was utilized in 13 patients (48.14%) where a diagnosis of borderline ovarian tumors was revealed in 8 patients. Recurrence was reported in one patient with serous type after approximately 26 months. The most common pathological type in our cohort was the mucinous borderline type which was reported in 14 patients (51.9%) followed by the serous type was reported in 11 patients (40.7%) and the seromucinous type in 1 patient only. Patients with mucinous borderline type were significantly younger (40.083±18.47 vs 53.73±11.91 years, p=0.028). Interestingly, Cancer Antigen 125 levels were significantly higher in mucinous than serous and seromucinous types (67(16-304) vs 20(6-294.6) U/ml, P=0.027). On the other hand, the radiological tumor size of serous and seromucinous type was larger than that of the mucinous type (23(19-31) cm vs 8(5-20) cm, P=0.001). Over a median follow up period of 58.66 (54.16-63.16) months, only one postoperative mortality was reported while only one recurrence was reported. Conclusion: Borderline ovarian tumors still represent a dilemma either in diagnosis or management. Frozen section examination could help to reach a preliminary diagnosis. Total abdominal hysterectomy and bilateral salpingo-oophorectomy is the cornerstone of surgical management, however, fertility-sparing surgery could be a valid option for women desiring fertility.